2022
DOI: 10.1016/j.euo.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Impact on Oncologic Outcomes of Persistently Elevated Prostate-specific Antigen After Salvage Lymph Node Dissection for Node-only Recurrent Prostate Cancer After Radical Prostatectomy: Clinical Implications for Multimodal Therapy

Abstract: Background: The optimal definition and prognostic significance of persistently elevated prostate-specific antigen (PSA) after salvage lymph node dissection (sLND) for node-only recurrent prostate cancer (PCa) remain unknown.Objective: To assess the definition and clinical implications of persistently elevated PSA after sLND for node-only recurrent PCa after radical prostatectomy. Design, setting, and participants: The study included 579 patients treated with sLND at 11 high-volume centers between 2000 and 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, the proportion of patients with locally progressive intermediate-risk and high-risk prostate cancer undergoing prostatectomy has recently increased considerably (17), which in turn has significantly increased the risk of postoperative PSM. Several studies have shown that postoperative PSM in prostate cancer is correlated with post-penetration Gleason score, PSA level, tumor infiltration in seminal vesicles, clinical stage of the tumor, size (volume) of the prostate, proficiency of the surgeon, the age and body mass index of the patient, and biopsy nerve infiltration (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportion of patients with locally progressive intermediate-risk and high-risk prostate cancer undergoing prostatectomy has recently increased considerably (17), which in turn has significantly increased the risk of postoperative PSM. Several studies have shown that postoperative PSM in prostate cancer is correlated with post-penetration Gleason score, PSA level, tumor infiltration in seminal vesicles, clinical stage of the tumor, size (volume) of the prostate, proficiency of the surgeon, the age and body mass index of the patient, and biopsy nerve infiltration (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up consisted of PSA testing 1 month after surgery, and, subsequently, further measurements were performed at time intervals of 3–6 months. PSA responders were defined by PSA decrease after sLND ≤0.3 ng/ml 18 . The administration of additional treatments after sLND was left at the discretion of each surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…PSA responders were defined by PSA decrease after sLND ≤0.3 ng/ml. 18 The administration of additional treatments after sLND was left at the discretion of each surgeon. Clinical recurrence (CR) after sLND was defined as positive conventional imaging in presence of a rising PSA, with patients censored on the date of last evidence of freedom from CR.…”
Section: Surgical Technique and Follow-upmentioning
confidence: 99%
“…With a cutoff of 0.3 ng/ml for the first postoperative PSA and a median follow-up of 48 months, men with persistently elevated PSA had a higher risk of cancer-specific mortality (hazard ratio 2.59) after sLND [32 ▪▪ ]. The authors demonstrated that early ADT use after sLND was beneficial for patients with PSA persistence after surgery (hazard ratio 0.49) [32 ▪▪ ].…”
Section: Cancer Control Outcomes In Patients Treated With Salvage Lym...mentioning
confidence: 97%
“…Gleason grade group 5 (hazard ratio 2.04), longer time from RP to PSA rise (hazard ratio 0.99), ADT for PSA rise after RP (hazard ratio 1.47), retroperitoneal uptake on PET/CT scan (hazard ratio 1.24), three or more positive spots on PET/CT imaging (hazard ratio 1.26), and higher PSA levels at sLND (hazard ratio 1.05; P < 0.0001) were found to be significant predictors of early clinical recurrence after sLND [21]. Recently, the same group found an inverse relationship between the first PSA after sLND and the probability of CSS [32 ▪▪ ]. With a cutoff of 0.3 ng/ml for the first postoperative PSA and a median follow-up of 48 months, men with persistently elevated PSA had a higher risk of cancer-specific mortality (hazard ratio 2.59) after sLND [32 ▪▪ ].…”
Section: Cancer Control Outcomes In Patients Treated With Salvage Lym...mentioning
confidence: 98%